Gerakan Pemuda sebagai Basis Promotif dan Preventif Pra Lansia dan Lansia - Farindira Vesti Rahmasari; Denny Anggoro P; Fadli Mahjud; Latifah Mutiara Haryanto (LPPM UMRI, 2020)
Non-communicable diseases such as heart disease, stroke, cancer, diabetes, and chronic obstructive pulmonary disease are the causes of death within nearly 75% in the world (WHO, 2018). In 2012, there were 29,546 cases of hypertension and 7,434 cases of diabetes happened in DIY. Based on Basic Health Research (Rikesdas), the prevalence of NCD increased from 2007 to 2013 and is expected to continuePeople with obesity, high blood pressure, high blood sugar level, high cholesterol, and a history of NCD in older people are at high risk of developing NCD.One of the effort in controlling NCD is prevention such as periodic health checking. NCD risk factors examination can be done through NCD Integrated Development Post (Posbindu) in the village. The results indicate that the average value before being educated is 44,17, while after being educated is 68,33. There was an increase of 24,16. These results indicate that the correlation between two variables yields 0.183 with probability value below 0.05, which states that the correlation between the previous and final values after educated is weak and there is obvious correlation. It is concluded that cadres’ knowledge and skill can be improved by training and continued by monitoring the cadre's skills observation field